Dinamika Psikologis Individu dengan Gangguan Kepribadian Ambang - Ni Luh Krishna Ratna Sari; Hamidah Hamidah; Adijanti Marheni (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2020)
Borderline personality disorder is one of the personality disorders that is widely encountered in psychiatric and psychological practices. This research aims to explore the psychological dynamics of individuals with borderline personality disorder based on the results of the assessment. The subject in this study is a 24-years-old man that showed the symptoms of borderline personality disorder. The research method used is qualitative with a case study approach. Data were collected through psychological assessment including interviews, observations, and some psychological tests such as graphic tests (BAUM, DAP, and HTP), SPM (Standart Progressive Matrices), SSCT (Sack's Sentence Completion Test), and Drawing Completion Test (DCT). The results showed that the subject had personality aspects such as emotional instability, low control of psychological drive, and the need to depend on others. Subjects have traumatic experiences such as abuse and early separation with parental figures, family dysfunction as well as unsupportive environmental factors. Interactions between these two conditions illustrate the psychological dynamics of the symptoms of borderline personality disorders addresses by subject. Keywords : Borderline personality disorder, traumatic experiences, young adulthood.